2020
DOI: 10.1177/1559325820939764
|View full text |Cite
|
Sign up to set email alerts
|

Application of Dexmedetomidine in Cardiopulmonary Bypass Prefilling

Abstract: Objective: The purpose of this study was to explore the application of dexmedetomidine (Dex) in cardiopulmonary bypass. Methods: A total of 60 patients undergoing elective cardiopulmonary bypass were divided into control (C) group and Dex group. In the Dex group, appropriate amount of Dex was added into the membrane lung prefilling solution before anesthesia induction, while those in control group were giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“… 4 Third, although the dosage of anesthetic (propofol and midazolam) used in this study was less in dexmedetomidine group than in the normal saline group, the criteria of administration of propofol and midazolam used in this study should be described. 1 This study reported that intraoperative blood pressure during cardiopulmonary bypass was lower in the dexmedetomidine group than in the normal saline group. 1 However, the pump flow and the magnitude of hemodilution during cardiopulmonary bypass in both groups should be described, because intraoperative blood pressure during cardiopulmonary bypass is mainly determined by pump flow and peripheral resistance associated with hemodilution.…”
mentioning
confidence: 76%
See 4 more Smart Citations
“… 4 Third, although the dosage of anesthetic (propofol and midazolam) used in this study was less in dexmedetomidine group than in the normal saline group, the criteria of administration of propofol and midazolam used in this study should be described. 1 This study reported that intraoperative blood pressure during cardiopulmonary bypass was lower in the dexmedetomidine group than in the normal saline group. 1 However, the pump flow and the magnitude of hemodilution during cardiopulmonary bypass in both groups should be described, because intraoperative blood pressure during cardiopulmonary bypass is mainly determined by pump flow and peripheral resistance associated with hemodilution.…”
mentioning
confidence: 76%
“…I read with interest the article, titled “Application of Dexmedetomidine in Cardiopulmonary Bypass Prefilling” by Wang et al, recently published in Dose-Response. 1 The highly-selective alpha-2 adrenoceptor agonist dexmedetomidine is widely used during the perioperative period to provide sedation and analgesia, for reduction of intraoperative stress, and to decrease the amount of anesthetic and opioid required. 2 The following comments, which may contribute to the bias in this study, should be considered while interpreting the results.…”
mentioning
confidence: 99%
See 3 more Smart Citations